FORMULASI STRATEGI DISTRIBUSI PRODUK SUSU BUBUK DI PT XYZ - Dwi Intan Widyastutie; Sahara; Kirbrandoko (School of Business, Bogor Agricultural University (SB-IPB), 2021)
Milk consumption in Indonesia is projected to increase by 4% annually. Responding to current conditions, PT XYZ as a powder milk producer in Indonesia must be able to increase sales volume. Currently, PT XYZ has 9 sales distribution areas. This research aims to analyze distribution strategy of PT XYZ 1) Analyze the distribution performance of PT XYZ in each distribution area; 2) Analyze internal and external factor are influencing the sales of PT XYZ; 3) Formulated distribution strategy for increase sales in PT XYZ. The methods used at this study were portfolio analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT, and Quantitative Strategic Planning Matrix (QSPM). Based on portfolio analysis, regions were located in four quadrants (regional 1, III, IV, and VI) were selected for further analysis. The four regions were analyzed by external and internal matrix, SWOT matrix and QSPM analysis. Then the best strategy was chosen in each region, regional I is to increase distribution density, the strategy chosen in regional III is to create a system related to product stock in branches. While in regional IV, namely increasing the availability of products in branches and in regional VI is strategy to increase the focus of distribution in medical branch (reduce return). Keywords: Powder Milk, Distribution, IFE, EFE, SWOT, QSPM